2020
DOI: 10.1111/jfpp.14770
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of anthocyanin profiles in şalgams (shalgams) produced with different production procedures

Abstract: Recently, studies on the research of traditional fermented foods and beverages with positive health effects have emerged. Not only the production and consumption of şalgam, but also the number of research on şalgam is increasing rapidly. There are two principal procedures used by producers for şalgam production: (1) the traditional and (2) the direct procedure. In the present study, individual and total anthocyanins in şalgams manufactured by traditional procedure, direct procedure, and addition of autochthono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…The amount of ethyl alcohol could not be detected at 15 and 20°C, while 0.15, 0.01, and 0.26 g/L were detected in şalgam fermented at 25, 30, and 35°C, respectively (p < .05). Our results were similar to previous studies (Tanguler et al, 2020;Tanguler, Gunes, et al, 2014) who reported the amount of ethyl alcohol between 0.19 and 7.30 g/L in şalgams.…”
Section: Composition Of şAlgamsupporting
confidence: 93%
See 2 more Smart Citations
“…The amount of ethyl alcohol could not be detected at 15 and 20°C, while 0.15, 0.01, and 0.26 g/L were detected in şalgam fermented at 25, 30, and 35°C, respectively (p < .05). Our results were similar to previous studies (Tanguler et al, 2020;Tanguler, Gunes, et al, 2014) who reported the amount of ethyl alcohol between 0.19 and 7.30 g/L in şalgams.…”
Section: Composition Of şAlgamsupporting
confidence: 93%
“…The dry matter amounts of the samples varied between 28.62 and 32.51 g/L. The results of dry matter analysis were in accordance with other studies related with şalgam which reported dry matter values of şalgam between 16.9 and 33.9 g/L Erten et al, 2008;Tanguler et al, 2020).…”
Section: Composition Of şAlgamsupporting
confidence: 90%
See 1 more Smart Citation
“…Shalgam has been deemed a functional food since it contains anthocyanin and phenolic compounds that provide health benefits to humans (Dereli et al, 2015;Ekinci et al, 2016;Kelebek et al, 2018;Kırca et al, 2007;Tazehkand & Valipour, 2019;Türker et al, 2004;Türkyılmaz et al, 2012). It was reported that the type of shalgam production methods affected anthocyanin quantity and profile in shalgam (Tangüler et al, 2021). Tanrıseven et al (2020) tested the effects of production methods on shalgam, resulting in the determination of seven different anthocyanins in shalgam.…”
Section: Introductionmentioning
confidence: 99%